Strain based triangular finite element for plate bending analysis. Issue 8 (15th April 2020) - Belounar, Abderahim; Benmebarek, Sadok; Belounar, Lamine
ABSTRACT: In this work, the formulation of a new triangular finite element is presented for static and free vibration of plate bending. The developed element which contains the three essential external degrees of freedom at each of the three corner nodes is based on the Reissner/Mindlin theory and the strain-based approach. This element is based on the linear variation of the three bending strains and constant transverse shear strains. The present element performances are evaluated through several tests related to moderated thick and thin plates with various shapes where it is found to be numerically more efficient than the bilinear element.